Peer-assisted Virtual Learning in Basic Surgical Skills for Medical Students in Malaysia during the COVID-19 Pandemic - Raymen Arviin Chandrasagran; Lim Yee Siew (Journal of Surgical Specialties and Rural Practice)
Introduction: During the coronavirus disease 2019 pandemic, all in-person teachings were suspended. This includes opportunities to learn surgical skills among undergraduate medical students in Malaysia. Virtual learning became the prime modality of medical education for all Malaysian universities. InciSioN Malaysia designed and conducted an online suturing workshop to increase medical students’ exposure to surgical skills. This workshop aimed to evaluate the feasibility and the reception of such workshops for undergraduate medical students in Malaysia.